Conditioning and learning in relation to disease - Ban, T A; Guy, W (Activitas nervosa superior, 1985)
Of the two generally recognized processes through which learning occurs--imprinting and conditioning--only the latter with its two paradigms, classical and operant, has both practical and heuristic implications for disease. From the classical conditioning experiments of Pavlov's laboratory over 100 years ago to the later work in operant conditioning by Skinner and others in the past four decades has evolved much of the basis of modern learning theory and its applications to disease in the form of behavior therapy. Variants of behavior therapy have been employed in the treatment of wide variety of medical and psychiatric illnesses. Recent developments in the study of brain function and biochemistry have led to renewed interest in the conditioning paradigm and its value as tool in these areas of research.
Keywords: homeostáza; učení; Social Behavior; Male; elektrokonvulzívní terapie; Dogs; Disease; Electroconvulsive Therapy; učení vyhýbat se; Homeostasis; mužské pohlaví; behaviorální terapie; posilování (psychologie); Avoidance Learning; Behavior Therapy; Animals; Learning; lidé; Humans; zvířata; Conditioning, Classical; Homosexuality; psi; klasické podmiňování; nemoc; sociální chování; Reinforcement, Psychology; homosexualita